Social Media and Political Parties: An Analysis of Twitter Utilization as Political Communication - Eldo, Dwian Hartomi Akta Padma (Jurnal Studi Ilmu Pemerintahan, 2024)
This studies aims to look at the activities of the @Gerindra Twitter account that utilizes Twitter as a digital communication medium for party branding. This research uses a descriptive qualitative method using the VOSViewer application as a research positioning and gap because digital communication research is not the first time. For the data analysis unit, the researcher used the NVivo 12 plus application to see the interactions carried out by the @Gerindra Twitter account. The results showed the transformation of the @Gerindra Twitter account, which previously only carried out branding activities using formal language and seemed rigid. However, the @Gerindra Twitter account has recently become a trending topic on Twitter several times because of its unusual communication style, which seems relaxed and not harsh. In addition, it also often tweets jokes that invite more and more Twitter user interactions. This shows that Gerindra's political party uses Twitter social media to communicate digitally with the public, especially millennials and Generation Z groups.